Between Resistance and Resilience. How Do Italian Solidarity Purchase Groups Change in Times of Crisis and Austerity? - Riccardo Guidi (Coordinamento SIBA, 2015)
This Paper deals with the current transformations of Solidarity Purchase Groups (SPGs) in Italy. We particularly wonder if and eventually how the economic crisis and austerity policies have affected SPGs. Through an approach based on the literature on political consumerism and social movements, six hypotheses are proposed: ‘less economic resources, less SPGs,’ ‘cultural path dependency,’ ‘increased op-portunities,’ ‘isomorphism,’ ‘civic traditions,’ and ‘resilience.’ Empirical data focus on Italian and Tuscan SPGs, by both articulating different research methods and focalizing on different levels. Although our work has only an explorative aim, our analysis shows that the amount of available economic resources cannot per se lead to a satisfying understanding of the evolution of SPGs. Hypotheses based on culture and politi-cal processes seem to be more promising and can point to the resilience capacity of those groups. Post-materialistic values resulting from economic well-being might have produced organized practices of political consumerism. However, once political consumerism gets structured—this is our tentative argument—not only does it resist to external shocks but also it transforms itself and adapts to the new conditions imposed by crises, that is, it becomes ‘resilient.’ The ‘resilience hypothesis’ applied to SPGs nevertheless has to face some social cleavages.